2017
DOI: 10.1111/jon.12456
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Pulsatility Index Is Elevated in Patients with Elevated Right Atrial Pressure

Abstract: BACKGROUND AND PURPOSE:Extracerebral venous congestion can precipitate intracranial hypertension due to obstruction of cerebral blood outflow. Conditions that increase right atrial pressure, such as hypervolemia, are thought to increase resistance to jugular venous outflow and contribute to cerebro-venous congestion. Cerebral pulsatility index (CPI) is considered a surrogate marker of distal cerebrovascular resistance and is elevated with intracranial hypertension. Thus, we sought to test the hypothesis that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…1,5 In this particular situation, a reduction in diastolic arterial blood flow velocities secondary to the increase in cerebral venous pressure resulted in a reduction of the PI. 13,14 These changes are similar to those seen in situations associated with intracranial hypertension. 15 The anastomotic stenosis was thought to be secondary to edema of the surrounding tissues.…”
Section: Case Descriptionssupporting
confidence: 73%
“…1,5 In this particular situation, a reduction in diastolic arterial blood flow velocities secondary to the increase in cerebral venous pressure resulted in a reduction of the PI. 13,14 These changes are similar to those seen in situations associated with intracranial hypertension. 15 The anastomotic stenosis was thought to be secondary to edema of the surrounding tissues.…”
Section: Case Descriptionssupporting
confidence: 73%
“…It has been confirmed that right atrium enlargement is usually in parallel with elevated right atrial pressure [27]. Moreover, elevated right atrial pressure indicates increased cerebrovascular resistance and cerebrovenous congestion [28]. It is supposed that dilated right atrium may indirectly reflect elevated right atrial pressure which impedes efflux of glymphatic drainage from PVS.…”
Section: Discussionmentioning
confidence: 97%
“…Cerebral hypoperfusion would be suspected if mean, systolic, and diastolic cerebral blood velocities of the middle cerebral artery are reduced as opposed to venous congestion where only diastolic cerebral blood velocities will be attenuated with the systolic values remaining unchanged. 14 During venous congestion and elevation in central venous pressure, diastolic cerebral blood velocity from TCD will be reduced and the pulsatility index ([systolic velocities -diastolic velocities]/mean velocities) (normal: 0.81-0.97) increased, 10,15 with reductions in both cerebral and somatic NIRS values. Similar signals will be observed 16 although somatic NIRS values would remain normal.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in PI can be associated with elevated intracranial pressure (ICP) or with elevation of the central venous pressure. [14][15][16]25,26 Global somatic desaturation will be present if the reduced TCD diastolic velocity and elevated PI is secondary to venous congestion. Nevertheless, global somatic saturation will be normal or maintained if the mechanism of brain desaturation, reduced TCD diastolic velocity, and elevated PI is secondary to intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%